Beyond the hospital walls: The lived experiences of Sidra's radiologists with home-based picture archiving and communication system during a global crisis - Alhamad, Ahmad; Al-Hamad, Areej; Yasin, Yasin M.; Iqbal, Zafar (Qatar Journal of Public Health)
Objective: This study explores the adaptation of radiologists at Sidra Medicine, Qatar, to the home-based picture archiving and communication system (HPACS) during the COVID-19 pandemic. Methods: This qualitative study used a phenomenological methodology to delve into the experiences of radiologists using HPACS, which emerged as a crucial tool for remote radiology practice during the pandemic. It highlights the perceived benefits, barriers, and challenges of using HPACS, and emphasizes its role in ensuring continuity of patient care and diagnostics while adhering to safety protocols. Results: The study reveals how HPACS facilitated work efficiency and safety, and also presented challenges such as workspace limitations and technical issues. The findings suggest a transformative impact of HPACS on the field of radiology, and indicate a future marked by increasingly digital and decentralized practices. Conclusion: This research contributes to understanding the adaptation of healthcare professionals to remote work technologies and provides insights for improving remote radiology systems and preparing for future crises.
Keywords: Qatar